2014
DOI: 10.1177/1099800413519495
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Mindfulness-Based Stress Reduction (MBSR) on Telomerase Activity in Women With Breast Cancer (BC)

Abstract: Mindfulness-based stress reduction (MBSR) reduces symptoms of depression, anxiety, and fear of recurrence among breast cancer (BC) survivors. However, the effects of MBSR (BC) on telomere length (TL) and telomerase activity (TA), known markers of cellular aging, psychological stress, and disease risk, are not known. This randomized, wait-listed, controlled study, nested within a larger trial, investigated the effects of MBSR (BC) on TL and TA. BC patients (142) with Stages 0–III cancer who had completed adjuva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
113
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(122 citation statements)
references
References 53 publications
5
113
0
4
Order By: Relevance
“…However, another study [38] reported that MBT had a small effect size (0.32) on reducing stress in adults with chronic conditions. Reviews of studies conducted with cancer patients suggested an even more significant effect of MBT on patient stress Regarding biomedical outcomes, some previous studies reported that MBSR training could increase plasma cortisol levels, extend cell longevity [40][41], promote the recovery of functional T cells [42], and improve plasma levels of IGF-1 and antigen-specific IgM and IgG 3 [43]. These M A N U S C R I P T…”
Section: Agreement and Disagreement With Other Systematic Reviewsmentioning
confidence: 92%
“…However, another study [38] reported that MBT had a small effect size (0.32) on reducing stress in adults with chronic conditions. Reviews of studies conducted with cancer patients suggested an even more significant effect of MBT on patient stress Regarding biomedical outcomes, some previous studies reported that MBSR training could increase plasma cortisol levels, extend cell longevity [40][41], promote the recovery of functional T cells [42], and improve plasma levels of IGF-1 and antigen-specific IgM and IgG 3 [43]. These M A N U S C R I P T…”
Section: Agreement and Disagreement With Other Systematic Reviewsmentioning
confidence: 92%
“…Further, these studies have often been non-randomized and not adequately controlled. These studies have generally found intervention-associated increases in PBMC basal TA (Epel, 2012; Epel et al, 2009b; Epel, 2009; Jacobs et al, 2011; Lengacher et al, 2014; Ornish et al, 2008; Schutte and Malouff, 2014b; Starkweather et al, 2014). A recent metaanalysis of four studies with randomized controlled designs (Jacobs et al, 2011; Daubenmier et al, 2012; Ho et al, 2012; Lavretsky et al, 2013) found an effect size of d= 0.46 for meditation intervention increasing PBMC basal TA (Schutte and Malouff, 2014b).…”
Section: Is Cellular Aging Preventable or Reversible?mentioning
confidence: 99%
“…Positive results in a small sample study such as this are intriguing, as they support the idea that telomere length could serve as an objective measure to be tracked over time to evaluate intervention efficacy, in addition to its potential role as a marker of health and disease. Lengacher et al [137] provided preliminary evidence that mindfulness-based stress reduction over 12 weeks increased telomerase activity in peripheral blood mononuclear cells from 142 breast cancer survivors.…”
Section: Effects Of Therapeutic Stress Reduction On Telomeresmentioning
confidence: 99%